Parent‐delivered early intervention in infants at risk for ASD: Effects on electrophysiological and habituation measures of social attention. Issue 5 (28th February 2017) - Jones, Emily J.H.; Dawson, Geraldine; Kelly, Jean; Estes, Annette; Webb, Sara Jane
Abstract : Prospective longitudinal studies of infants with older siblings with autism spectrum disorder (ASD) have indicated that differences in the neurocognitive systems underlying social attention may emerge prior to the child meeting ASD diagnostic criteria. Thus, targeting social attention with early intervention might have the potential to alter developmental trajectories for infants at high risk for ASD. Electrophysiological and habituation measures of social attention were collected at 6, 12, and 18 months in a group of high‐risk infant siblings of children with ASD ( N  = 33). Between 9 and 11 months of age, infant siblings received a parent‐delivered intervention, promoting first relationships (PFR), ( n  = 19) or on‐going assessment without intervention ( n  = 14). PFR has been previously shown to increase parental responsivity to infant social communicative cues and infant contingent responding. Compared to infants who only received assessment and monitoring, infants who received the intervention showed improvements in neurocognitive metrics of social attention, as reflected in a greater reduction in habituation times to face versus object stimuli between 6 and 12 months, maintained at 18 months; a greater increase in frontal EEG theta power between 6 and 12 months; and a more comparable P400 response to faces and objects at 12 months. The high‐risk infants who received the intervention showed a pattern of responses that appeared closer to the normative responses of two groups of age‐matched low‐risk control participants. Though replication is necessary, these results suggest that early parent‐mediated intervention has the potential to impact the brain systems underpinning social attention in infants at familial risk for ASD. Autism Res 2017, 10: 961–972 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.